Analisis Sebaran Total Suspended Particulate (TSP) Dengan Model Gaussian Point Source Di Pembangkit Listrik Berbahan Bakar Biomassa - Shindy Zellia; Ivan Indrawan; Lies Setyowati; Muhammad Faisal; Isra' Suryati (Universitas Andalas, 2018)
The study aims to analyze the concentration of TSP generated from the smokestacks of biomass fuelled power plant with 2 x 15 MW capacity along with the pattern of distribution in the ambient air around the plant. The field observation conducted in Jl. K. L. Yos Sudarso KM 10.5 by making five (5) ambient air sample point, the point I is located around 130 m south, the point II within 220 m south, point III around 110 m east, point IV around 325 m north and point V around 100 m west from sources emissions. The sample is taken for 3 (three) days, i.e in the morning, afternoon and evening. Maximum TSP concentration was measured at point III at 50,93 μg/m3. Meanwhile, according to Gaussian Point Source model, the maximum TSP concentration at point I is around 1,79 μg/m3. The concentration of TSP is still below the ambient air quality standard. Furthermore, the measured TSP concentration and TSP modeling were mapped with the Surfer program version 11.0. Based on the results, the measured TSP concentration mapping indicates that the highest affected area is located at the eastern region of the emission source. Moreover, Mapping of TSP concentration models show that the highest affected area is located at the southern part of the emission source.